An Overview of Missed Nursing Care and Its Predictors in Saudi Arabia: A Cross-Sectional Study - Essa H. Al Muharraq; Sultan M. Alallah; Saad A. Alkhayrat; Ali G. Jahlan (Hindawi Limited, 2022)
Background. Nursing care is holistic, and missing any aspect of care can be critical to patients' health. However, due to the complex and intense nature of the nursing practice, nurses have to unintentionally prioritize some activities, forcing them to omit some aspects of nursing care. Aim. To explore the dimensions of missed nursing care and its predictors within the Saudi Arabian healthcare system. Methods. Quantitative, cross-sectional study used the MISSCARE survey by utilizing nonprobability convenience sampling to collect the data of 604 staff nurses working in inpatient wards in Jazan, Saudi Arabia. Results. The overall mean of missed nursing care is (m = 1.37, SD = 0.45). Missed nursing care activities were mostly failure to attend interdisciplinary care conferences (m = 1.66, SD = 0.96) and patient ambulation thrice a day (m = 1.63, SD = 0.97). Missed nursing care was mainly caused by human resource shortage (m = 3.53, SD = 0.88). Missed nursing care is predicted by the turnover intention (B = 2.380, t = 3.829, p<001) and job satisfaction (B = −0.864, t = −4.788, p<001). Conclusion. Although missed nursing care is evident in Saudi Arabia, it is significantly lower than the international rates, and it is mainly caused by labor resource shortage which directly influences nurses' job satisfaction and intention to leave. Optimizing the recruitment process, resource allocation and effective nurses' retention programs are proposed solutions that may be beneficial to mitigate missed nursing care.